BLN la competencia y su impacto en el rendimiento académico en los estudiantes del noveno año de educación general básica de la Unidad Educativa Municipal ciudad de Quevedo - Villacis Albiño, Mónica (2018)
The format of this type of program is the same in most national channels and although the contests are different the end does not vary "compete to win". In the reality show BLN the Competition many young people are nominated as contestants of the program, the television channels call the public viewer to make a demonstration of their talents and in this way to determine if the applicant has the necessary qualities that allow him to enter the program ; This is known as "casting" which is attended by millions of young people with the intention of being part of it and only people who have the predetermined profile that production requires and that more than talent or skill is necessary to have a good body worked up; that is, girls with a flat abdomen and a thin waist; guys with defined bodies, graceful and with charisma that can project a lot of personality through the screen. The problem lies in what is the impact of BLN the Competition on the academic performance of the students of the City of Quevedo Municipal Educational Unit, the general objective is to determine the impact that BLN has on the academic performance of the students of the Municipal Educational Unit City of Quevedo. To this end, several research tools have been used, such as: inductive and deductive methods, and types of research, such as descriptive and field research, were conducted on the 9th EGB students of the educational unit. For this a series of sizes is proposed in order to make them aware that the reality show guys are not good role models, and that they should concentrate more on the studies than on seeing BLN La Competencia.